2018
DOI: 10.1016/j.jse.2018.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Major complications after distal biceps tendon repairs: retrospective cohort analysis of 970 cases

Abstract: Distal biceps repair is associated with a 7.5% major complication rate and 4.5% reoperation rate. The use of a 2-incision technique for repair increases the risk of radioulnar synostosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
46
2
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 15 publications
1
46
2
7
Order By: Relevance
“…Other papers have also noted that the single incision repair technique, used in all cases in this cohort, is associated with greater rates of lateral antebrachial cutaneous neuropraxia. 14 This may explain the rate at the higher end of that described by other papers. 9,14,17 There were no reported posterior interosseous nerve injuries.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Other papers have also noted that the single incision repair technique, used in all cases in this cohort, is associated with greater rates of lateral antebrachial cutaneous neuropraxia. 14 This may explain the rate at the higher end of that described by other papers. 9,14,17 There were no reported posterior interosseous nerve injuries.…”
Section: Discussionmentioning
confidence: 66%
“…14 This may explain the rate at the higher end of that described by other papers. 9,14,17 There were no reported posterior interosseous nerve injuries.…”
Section: Discussionmentioning
confidence: 66%
“…Historically, the single-incision approach is associated with increased nerve injury, most commonly the lateral antebrachial cutaneous (LABC) nerve and radial sensory nerve, while the double-incision is associated with an increased rate of proximal radioulnar synostosis, heterotopic ossification, and stiffness with supination/pronation. 6,8,10,19 Notably, while the overall complication rate is relatively high, the incidence of complications leading to revision surgery is comparatively low. 3,5 Thus, there are few data available with regard to the clinical outcomes after revision surgery.…”
mentioning
confidence: 99%
“…Although this technique may have reduced the risk of nerve injury, it requires dissection through the radioulnar syndesmosis and has been reported to increase the risk for heterotopic ossification (HO). 1,6,7 To date, no surgical technique has been proven superior, and results with sufficient long-term follow-up are lacking. The purpose of this study was to evaluate patient-reported long-term outcomes 10 years after distal biceps tendon repair using the modified double-incision technique described by Morrey et al 17…”
mentioning
confidence: 99%
“…Although this technique may have reduced the risk of nerve injury, it requires dissection through the radioulnar syndesmosis and has been reported to increase the risk for heterotopic ossification (HO). 1 , 6 , 7 …”
mentioning
confidence: 99%